2022
DOI: 10.1021/acsanm.2c01965
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Thermal Stability and Dissociation Mechanisms of Purified Boron Nitride Nanotubes: Implications for High-Temperature Nanocomposites

Abstract: A fundamental understanding of the thermal behavior of reinforcement materials is crucial to fully exploit their properties in composites. Boron nitride nanotubes (BNNTs), structural analogues to carbon nanotubes, are a strong candidate for nanofillers in high-temperature composites due to their high thermal stability, oxidation resistance, excellent mechanical properties, and high thermal conductivity. In this paper, samples of high-quality, high-purity BNNTs were tested to thermal failure in an inert atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…While sintering the silica particles, the stability of the fillers must be confirmed at high temperatures to prevent nanofillers from being damaged. Previously, studies have reported that the BNNTs have high oxidation resistance of ∼850 • C [16,17], and a recent study confirms the complete stability of the BNNTs up to 1800 • C in inert environments [19]. In order to prevent oxidation of BNNTs above 850 • C in air during the sintering process, the sintering process was divided into two steps (1) polymer burnout stage in the air up to 750 • C (figure 4 The green state samples first underwent a polymer burnout cycle where samples were heated at a 2 • C ramp rate up to 750 • C with a hold of 2 h at 240 • C and 1 h at 300 • C in a Lindberg/Blue M box furnace (ThermoFisher Scientific, Waltham, MA) in air to burn out binder polymer from the printed samples.…”
Section: Polymer Burnout and Ceramic Fusingmentioning
confidence: 70%
See 1 more Smart Citation
“…While sintering the silica particles, the stability of the fillers must be confirmed at high temperatures to prevent nanofillers from being damaged. Previously, studies have reported that the BNNTs have high oxidation resistance of ∼850 • C [16,17], and a recent study confirms the complete stability of the BNNTs up to 1800 • C in inert environments [19]. In order to prevent oxidation of BNNTs above 850 • C in air during the sintering process, the sintering process was divided into two steps (1) polymer burnout stage in the air up to 750 • C (figure 4 The green state samples first underwent a polymer burnout cycle where samples were heated at a 2 • C ramp rate up to 750 • C with a hold of 2 h at 240 • C and 1 h at 300 • C in a Lindberg/Blue M box furnace (ThermoFisher Scientific, Waltham, MA) in air to burn out binder polymer from the printed samples.…”
Section: Polymer Burnout and Ceramic Fusingmentioning
confidence: 70%
“…It was estimated that the dissociation of the B-N bond and failure of nanotubes occurred at temperatures up to 1900 • C depending on tube geometry. A recent study reported that B-N structures of BNNTs are completely stable up to 1800 • C in inert environments, introducing confident use of high-temperature manufacturing processing on BNNT composites [19].…”
Section: Introductionmentioning
confidence: 99%
“…To prepare the SiC-BNNT composites, BNNTs (Figure a) were dispersed in acetone with probe sonication. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of the BNNTs were shown in an earlier publication . The BNNT/acetone dispersion (Figure b) was added with a commercial poly­(carbosilane) preceramic polymer (SMP-10, Starfire) and thoroughly mixed with probe sonication.…”
Section: Discussionmentioning
confidence: 99%
“…1(a)). 14,15 Their high thermal conductivity and mechanical strength make them suitable for applications in various fields, such as electronics, energy storage, and biomedicine. [16][17][18][19][20][21][22][23] This comprehensive review seeks to delve into the intricate world of BNNTs, with a particular focus on their growth methodologies and applications in neutron shielding, particularly in aerospace engineering and cancer therapy (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)). 14,15 Their high thermal conductivity and mechanical strength make them suitable for applications in various fields, such as electronics, energy storage, and biomedicine. 16–23…”
Section: Introductionmentioning
confidence: 99%